Evaluating the Efficiency of Alkaline Activator with Silica-Rich Wastes in Stabilizing Cadmium-Contaminated Soil - Khitam Saeed; Sahar Al-Khyat; Zuhair Abd Hacheem; Sabah H. Fartosy (Civil Engineering Journal, 2024)
Contaminant soil remediation has potential engineering applications with various stabilization techniques addressing heavy metal contamination. Conventional soil stabilizers, however, have an environmental impact, promoting international research into environmentally friendly alternatives. Using waste byproducts to produce geopolymer binders as new green cementitious materials can provide an environmentally friendly and effective option for soil improvement. Silica-rich wastes have been advanced as a sustainable option for soil stabilization. The effectiveness of alkaline-activated silica-rich wastes in stabilizing cadmium-contaminated soil and its potential engineering utilization remain of profound significance, demanding sustained and rigorous research investigation. Cadmium was immobilized in silty clay soil by rich silica waste products—fly ash, silica fume, and rice husk ash—at various percentages with 4.5 and 6.5-molar alkaline activators. Unconfined compressive strength tests assessed soil behavior, while Toxicity Characteristic Leaching Procedure (TCLP), pH tests, X-ray diffraction, and scanning electron microscope analyses explained cadmium immobilization mechanisms. The experimental results revealed that alkali-activated silica-rich wastes enhanced strength and cementitious properties and reduced cadmium leaching in the contaminated silty clay. The Finite Element Method was also employed to analyze the bearing capacity of the stabilized contaminated soil. The numerical results support the experimental results and confirm increased soil strength and reduced compressibility, endorsing the efficacy of the stabilization techniques and environmental benefits. Doi: 10.28991/CEJ-2024-010-07-04 Full Text: PDF